A sustainability rereading of agrarian production systems - Silva, Elizabete Maria da; Vieira, Eloir Trindade Vasques; Tashima, Lucélia da Costa Nogueira; Guilherme, Denilson de Oliveira (Interações, 2017)
This review criticizes the origin and insertion of agricultural production systems and local development. It is concluded that these have met socioeconomic and environmental requirements. Conventional agriculture supplies food needs, but faces serious socio-environmental problems. Precision agriculture, more rational, is not feasible for small producers. Organic agriculture, which is more sustainable, does not compete with conventional production.